Sexual and Family Diversity in Education: Attitudes of University Students in Teacher Training - Rodríguez Zambrano , Arturo Damián; Villafuerte Holguín, Jhonny Saulo; Flor Unda , Omar Cristobál (Journal of Ecohumanism, 2024)
The objective of the present study is to examine attitudes towards sexual and family diversity in Ecuadorian students and its relationship with variables such as type of training program, age, gender, among others. For this study, the information obtained from a group of university students belonging to the pedagogy career has been considered. A quantitative approach within the naturalistic paradigm was used to explore the dimensions of (1) family diversity, (2) personal attitudes towards sexual diversity, and (3) predictive factors of institutional stance towards addressing sexual diversity. Surveys and Likert-type questionnaires were administered to a sample of 637 participants, including students and teachers of both sexes, aged between 18 and 54 years, affiliated with a public university in Ecuador. A nonparametric analysis of the data was presented, which revealed significant differences according to sex, age and study program. Likewise, a correlation was found between age and attitude towards sexual and family diversity of future teachers. This underlines the importance of developing positive attitudes towards sexual and family diversity in teacher training programs, with a focus on inclusion and attention to diversity.